(untitled) (KMC Journal, 2025)
Innovative pedagogical approaches to language teaching stress fostering communication abilities and contextual usage of language. This qualitative narrative study explores English language teachers’ perceptions and practices of textbook use in Nepali secondary schools. Four secondary level English language teachers were purposively selected as the participants from public schools in Kanchanpur district, Nepal. I employed narrative interview protocols with open-ended questions and classroom observation as research tools for collecting necessary data, and the data were analysed and interpreted using thematic analysis. The findings of the study showed that English language teachers have been entirely dependent on texts and exercises of the prescribed textbooks in their classroom practices. The study also revealed that English teachers have positive perceptions and knowledge of curriculum objectives and textbook alignment, but in classroom pedagogy, they fail to teach language through the given content and tasks. The study further showed that English language teachers spent more time explaining the content rather than focusing on language learning activities. The study implies that English teachers at secondary level need to employ student-centred innovative approaches creating language learning environment in the classroom, and engage students in activities using textbook contents and tasks, and even going beyond the textbook tasks.